ELASTIC-DISSIPATIVE STABILIZATION OF DYNAMIC PROCESSES OF HYDROPULSE SYSTEMS OF MINING MACHINES - SHEVCHUK, Stepan; SLIDENKO, Viktor (My University, 2018)
Investigation of elastic-dissipative stabilization of dynamic processes of hydropulse systems of mining machines.
Keywords: stabilization; stiffness; dissipation; hydraulic hammer; waveguide; heterogeneous lyophobic system